Erzhi pills reverse PD-L1-mediated immunosuppression in melanoma microenvironment - Zhirui Fang; Yuejin Xue; Yuze Leng; Lusha Zhang; Xiuyun Ren; Ning Yang; Jing Chen; Lu Chen; Hong Wang (Heliyon, 2024)
Background: Cancer immunotherapies aimed at activating immune system, especially by blocking immune checkpoints, have become a successful modality for treating patients with advanced cancers. However, its clinical practice is frequently conceded by high outcomes, low initial response rates and severe side effects. New strategies are necessary to complement and advance this biological therapy. Erzhi Pills (EZP) have diverse pharmaceutical effects including immune regulation, anti-tumor and anti-senescence. We hypothesized that EZP could exert its antitumor effect through immunomodulation. Purpose: The aim of this study was to investigate the effects of EZP on anti-tumor activities, and define its molecular mechanisms. Methods: By applying melanoma model with high immune infiltrates, we determined the anti-melanoma effect of EZP. To identify whether this effect was mediated by direct targeting tumor cells, cell viability and apoptosis were examined in vitro. Network pharmacology analysis was used to predict the potential mechanisms of EZP for melanoma via immune response. Flow cytometry, immunohistochemistry (IHC), enzyme-linked immunosorbent assay (ELISA) and crystal violet (CV) experiments were performed to detect T cell infiltrations and functions mediated by EZP. The mechanism of EZP was further investigated by western blotting both in vivo and in vitro. Results: The administration of EZP significantly inhibited tumor weight and volume. EZP extract could only slightly reduce cell viability and induce melanoma apoptosis. Network pharmacology analysis predicted that JAK-STAT signaling pathway and T cell receptor signaling pathway might be involved during EZP treatment. Flow cytometry and IHC analyses showed that EZP increased the number of CD4+ T cells and enhanced the function of CD8+ T cells. In co-culture experiments, EZP elevated killing ability of T cells. Western blotting showed that EZP treatment reduced PD-L1 signaling pathway. Conclusion: These ﬁndings indicated that EZP exerted anti-melanoma effects by inducing apoptosis and blocking PD-L1 to activate T cells. EZP might represent a promising candidate drug for cancer immunotherapies.